PERANCANGAN E-LEARNING BERBASIS WEB DI SMK SIDRATUL MUNTHAHA YAPIS WAMENA PAPUA DENGAN METODE BLACKBOX - Syarifah Syarifah; Kurniadin Abd Latif (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2024)
In the era of technology which is developing rapidly in all fields, the learning process in the 3T Region, especially Sidratul Munthaha Yapis Wamena Papua Vocational School, still carries out a conventional learning process. This means that some students and teachers are not optimal in recognizing and implementing technology in the field of education. E-learning has developed and been applied in various schools. However, this convenience is not yet fully felt by students and teachers in Wamena Papua. The aim of this research is to design web-based e-learning and test the service level of the e-learning system using the black box method. The design method used is the waterfall method with stages of analysis, design, coding and testing. Testing was carried out using the black box method. The research results show that there are five interface displays for e-learning that have been designed, consisting of the homepage display, login page, classroom creation form, material posting form, and attendance display. Based on the results of black box testing, it proves that the e-learning system can be used according to the expected function. However, there are several notes on the design of this e-learning from media experts, including: the need to provide validation of assignment descriptions, automate assignment publication times, provide information on assignment collection pages, and automate assignment upload times.